Anti-inflammatory and Antioxidant Properties of Probiotic Bacterium Lactobacillus mucosae AN1 and Lactobacillus fermentum SNR1 in Wistar Albino Rats - Ayyanna, Repally; Ankaiah, Dasari; Arul, Venkatesan (Frontiers in Microbiology, 2018)
The potent antioxidant probiotic strains Lactobacillus mucosae AN1 and Lactobacillus fermentum SNR1 were assessed for anti-inflammatory properties in carrageenan (acute) and complete Freund’s adjuvant-induced inflammation (chronic) models in the present study. The two probiotic strains were administered orally along with feed to the Wistar albino male rats as whole cell as well as microencapsulated form. The following experiments were performed to evaluate the anti-inflammatory properties of probiotic strains and the results were observed that the encapsulated and unencapsulated probiotic strains have exhibited statistically significant decrease in paw thickness. Percentage of inhibition in paw thickness of microencapsulated probiotic bacteria (Group VIII), unencapsulated strains (Group IX) were revealed 85 ± 13% and 77 ± 25%, respectively. In Hematoxylin and Eosin staining, results were revealed that the probiotic strains were exhibited anti-inflammatory effects on inflammation-induced paw tissues. qRT-PCR studies revealed upregulation of anti-inflammatory cytokine genes and down-regulation pro-inflammatory cytokine genes in probiotic-treated rat paw tissues. Further, the expression of anti-inflammatory and pro-inflammatory cytokines were examined using immunohistochemistry and ELISA methods. The probiotic administered rat paw tissue in different groups have exhibited the low level of lipid peroxides formation and higher anti-oxidant activities when compared to the control and inflammation control tissues.